2006
DOI: 10.1016/j.ejvs.2005.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive Resuscitation in Patients with Ruptured Abdominal Aortic Aneurysm

Abstract: Animal studies demonstrate superiority of hypotensive resuscitation over aggressive resuscitation but further research is required to assess its efficacy in patients with ruptured AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 29 publications
0
27
0
2
Order By: Relevance
“…The initial resuscitation strategy most commonly adopted in patients with rAAA across vascular units is ''permissive hypotension.'' 18 Such hypotension may well result in hypoperfusion and early coagulopathy, although unlike patients with trauma, evidence in the rAAA cohort demonstrates no significant relationship between hypotension and/or hypoperfusion, the degree of coagulopathy, and fibrinolytic parameters. In addition, an earlier suggestion about elevation of fibrinolytic factors in rAAAs could be related to the application of supraceliac cross clamp that in turn reduces the hepatic blood flow and results in elevation of fibrinolytic factors.…”
Section: Discussionmentioning
confidence: 97%
“…The initial resuscitation strategy most commonly adopted in patients with rAAA across vascular units is ''permissive hypotension.'' 18 Such hypotension may well result in hypoperfusion and early coagulopathy, although unlike patients with trauma, evidence in the rAAA cohort demonstrates no significant relationship between hypotension and/or hypoperfusion, the degree of coagulopathy, and fibrinolytic parameters. In addition, an earlier suggestion about elevation of fibrinolytic factors in rAAAs could be related to the application of supraceliac cross clamp that in turn reduces the hepatic blood flow and results in elevation of fibrinolytic factors.…”
Section: Discussionmentioning
confidence: 97%
“…Cautious fluid administration is recommended in patients with cardiac dysfunction. Bitoh et al 72 reported left ventricular diastolic dysfunction, measured using the mitral annular velocity by tissue Doppler method, after unclamping in eight patients undergoing infrarenal AAA repair and the dysfunction persisted until the end of the surgery. Pulmonary edema occurred in two of their patients with the lowest tissue Doppler mitral annular velocity.…”
Section: Aortic Unclampingmentioning
confidence: 98%
“…This can lead to further hemorrhage and rapid decompensation prior to definitive therapy. Permissive hypotension [ 10 ], allowing the patient with a ruptured abdominal aortic aneurysm to maintain a systolic blood pressure of ~80-90 mmHg, is preferred so long as the patient displays appropriate mentation and maintains systemic and peripheral perfusion. This approach allows for temporary stabilization of the patient and time to obtain a CTA and formulate a plan of approach to repair.…”
Section: Ruptured Aaamentioning
confidence: 99%